The beneficial effect of fluoxetine on behavioral and cognitive changes in chronic experimental Chagas disease unveils the role of serotonin fueling astrocyte infection by Trypanosoma cruzi. - Glaucia Vilar-Pereira; Daniel Gibaldi; Leda Castaño-Barrios; Andrea Alice da Silva; Isabela Resende Pereira; Otacílio Cruz Moreira; Constança Britto; Hílton Antônio Mata Dos Santos; Raquel de Oliveira Lopes; Luzineide Wanderley Tinoco; Wilson Oliveira; Joseli Lannes-Vieira (Public Library of Science (PLoS), 2024)
Background In Chagas disease (CD), a neglected tropical disease caused by the parasite Trypanosoma cruzi, the development of mental disorders such as anxiety, depression, and memory loss may be underpinned by social, psychological, and biological stressors. Here, we investigated biological factors underlying behavioral changes in a preclinical model of CD. Methodology/principal findings In T. cruzi-infected C57BL/6 mice, a kinetic study (5 to 150 days postinfection, dpi) using standardized methods revealed a sequential onset of behavioral changes: reduced innate compulsive behavior, followed by anxiety and depressive-like behavior, ending with progressive memory impairments. Hence, T. cruzi-infected mice were treated (120 to 150 dpi) with 10 mg/Kg/day of the selective serotonin reuptake inhibitor fluoxetine (Fx), an antidepressant that favors neuroplasticity. Fx therapy reversed the innate compulsive behavior loss, anxiety, and depressive-like behavior while preventing or reversing memory deficits. Biochemical, histological, and parasitological analyses of the brain tissue showed increased levels of the neurotransmitters GABA/glutamate and lipid peroxidation products and decreased expression of brain-derived neurotrophic factor in the absence of neuroinflammation at 150 dpi. Fx therapy ameliorated the neurochemical changes and reduced parasite load in the brain tissue. Next, using the human U-87 MG astroglioma cell line, we found no direct effect of Fx on parasite load. Crucially, serotonin/5-HT (Ser/5-HT) promoted parasite uptake, an effect increased by prior stimulation with IFNγ and TNF but abrogated by Fx. Also, Fx blocked the cytokine-driven Ser/5-HT-promoted increase of nitric oxide and glutamate levels in infected cells. Conclusion/significance We bring the first evidence of a sequential onset of behavioral changes in T. cruzi-infected mice. Fx therapy improves behavioral and biological changes and parasite control in the brain tissue. Moreover, in the central nervous system, cytokine-driven Ser/5-HT consumption may favor parasite persistence, disrupting neurotransmitter balance and promoting a neurotoxic environment likely contributing to behavioral and cognitive disorders.